2021
DOI: 10.1021/acs.chas.1c00021
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from the Explosion that Occurred during the Synthesis of Diaminomethanesulfonic Acid: Discussion and Preventative Strategies

Abstract: A violent explosion accident occurred when diaminomethanesulfonic acid was synthesized from diaminomethanesulfinic acid and hydrogen peroxide. In this work, we reviewed all the reported methods of synthesizing diaminomethanesulfonic acid and analyzed the causes of the explosion in detail from the reaction mechanisms and operations. In the end, strategies were proposed to avoid underlying explosion incidents in relevant experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In this strategy, low-cost solutions were implemented by a Hygiene and Safety Internal Advising Committee (H&SIAC) to help prevent and reduce safety hazards . Despite these efforts in the chemical sciences, including the fact that many laboratory courses have been converted to online due to the COVID-19 pandemic, recent literature reports involving laboratory incidents and poor safety culture attitudes. For example, Artdej has investigated the safety study survey of 27 fourth year undergraduate students enrolled in chemistry laboratory courses and found that most students misunderstood the meaning of hazardous chemicals and faced difficulties in matching the safety signs . Peter et al also studied the chemical safety awareness and best practices of 1247 secondary school students in urban and rural Nigerian schools and found that rural area students have lower levels of chemical safety awareness compared to their urban counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy, low-cost solutions were implemented by a Hygiene and Safety Internal Advising Committee (H&SIAC) to help prevent and reduce safety hazards . Despite these efforts in the chemical sciences, including the fact that many laboratory courses have been converted to online due to the COVID-19 pandemic, recent literature reports involving laboratory incidents and poor safety culture attitudes. For example, Artdej has investigated the safety study survey of 27 fourth year undergraduate students enrolled in chemistry laboratory courses and found that most students misunderstood the meaning of hazardous chemicals and faced difficulties in matching the safety signs . Peter et al also studied the chemical safety awareness and best practices of 1247 secondary school students in urban and rural Nigerian schools and found that rural area students have lower levels of chemical safety awareness compared to their urban counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions will also drive the release of gas, from both hydrogen peroxide and Caro’s acid, , and can trigger thermal runaway in hydrogen peroxide, a chain reaction leading to explosion . Released gas can overpressurize containers, leading to explosion, as occurred in the recent case involving Piranha catalyzed synthesis and the explosion of a Piranha waste bottle at the University of Kentucky . The 1999 explosion of a Japanese tank-car carrying hydrogen peroxide was triggered by the mixing of 1 × 10 –4 M CuCl 2 with hydrogen peroxide …”
Section: Piranha Hazardsmentioning
confidence: 99%
“…However, these are inherently reactive materials which can be hazardous to transport, store and use, and have been responsible for laboratory accidents in recent years. [5][6][7] In an analysis of accidents that occurred in the Chinese Chemical Industry between 2006-2017, it was reported that 340 (>8%) 'casualty accidents' were associated with oxidants and organic peracids. 8 Explosions of organic peroxides at the Arkema plant in Texas during the tropical storm 'Harvey' in 2017 9 and the devastation caused by the explosion of ammonium nitrate in Beirut in 2020 10,11 have also highlighted, in a very public way, the dangers of stockpiling large volumes of oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Caro's acid, H 2 SO 5 ), is known to be an extremely hazardous oxidant, prone to explode spontaneously. 5 In 2008, Page, Marken and co-workers first described the use of electrochemically-generated percarbonate and persulfate oxidants for the asymmetric epoxidation of an alkene (1-phenylcyclohexene). 18 Employing a boron-doped diamond (working) anode and a Pt cathode in an undivided electrochemical cell, a constant potential of 5 V was applied to convert sulfuric acid into PDS, which was deployed for the epoxidation reaction after adjusting the pH to between 7-9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation